2019
DOI: 10.1080/15548627.2019.1596484
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagy during mitosis via CUL4-RING ubiquitin ligases-mediated WIPI2 polyubiquitination and proteasomal degradation

Abstract: Macroautophagy/autophagy is a cellular process in which cytosolic contents are degraded by lysosome in response to various stress conditions. Apart from its role in the maintenance of cellular homeostasis, autophagy also involves in regulation of cell cycle progression under nutrient-deprivation conditions. However, whether and how autophagy is regulated by the cell cycle especially during mitosis remains largely undefined. Here we show that WIPI2/ATG18B (WD repeat domain, phosphoinositide interacting 2), an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 84 publications
0
44
0
Order By: Relevance
“…Ubiquitin ligase MKRN1 regulates translating ribosome by recognizing, binding and promoting ubiquitination of its substrate PABPC1 [11]. Ubiquitin ligase Speckle-type BTB-POZ protein (SPOP) limits inflammation by promoting ubiquitination of the innate signal transducer, myeloid differentiation primary response protein 88 (MYD88) [12].During mitosis induction, ubiquitin ligase CUL4-RING (CRL4s) raises the direct substrate WIPI2/ ATG18B (WD repeat domain, phosphoinositide interacting 2), an autophagy-related (ATG) protein that plays a critical role in autophagosome biogenesis through DDB1 (damage specific DNA binding protein 1), thus leading to the polyubiquitination and proteasome degradation of WIPI2 and inhibiting autophagy [13]. It has been proved that many of ubiquitin ligases are closely related to tumor development, malignant phenotype, and cisplatin resistance in cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin ligase MKRN1 regulates translating ribosome by recognizing, binding and promoting ubiquitination of its substrate PABPC1 [11]. Ubiquitin ligase Speckle-type BTB-POZ protein (SPOP) limits inflammation by promoting ubiquitination of the innate signal transducer, myeloid differentiation primary response protein 88 (MYD88) [12].During mitosis induction, ubiquitin ligase CUL4-RING (CRL4s) raises the direct substrate WIPI2/ ATG18B (WD repeat domain, phosphoinositide interacting 2), an autophagy-related (ATG) protein that plays a critical role in autophagosome biogenesis through DDB1 (damage specific DNA binding protein 1), thus leading to the polyubiquitination and proteasome degradation of WIPI2 and inhibiting autophagy [13]. It has been proved that many of ubiquitin ligases are closely related to tumor development, malignant phenotype, and cisplatin resistance in cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of the CCNB1 gene could inhibit cell proliferation (Li et al, 2019), suggesting that CCNB1 could regulate cell cycle and affect cell proliferation. Furthermore, CCNB1 is involved in regulating autophagy (Lu et al, 2019), which in turn regulates the degree of tissue fibrosis (Qin et al, 2017). Apoptosis of tracheal epithelial cells can promote the proliferation of fibroblasts, thereby aggravating TS (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The HUWE1-mediated ubiquitination depends on WIPI2 phosphorylation by MTOR at S395, and this provides another explanation for how MTOR inhibits autophagy [ 167 ]. A more recent study demonstrated that WIPI2 is a substrate of CUL4-RING ubiquitin ligase, which is activated upon mitosis induction and promotes the K48-linked polyubiquitination of WIPI2 and its degradation, again inhibiting autophagy [ 168 ].…”
Section: Ubiquitination In the Regulation Of Autophagymentioning
confidence: 99%